Genetics of grain yield and its component traits in drought tolerance rice - Arsode, Pandurang B; Singh, Ravi P; Singh, SK; Kumar, Manish; Namrata; Choudhary, Madhu; Jena, Debarchana; Singh, Vineeta; Rout, Diptibala; Sahoo, Biswajit; Nanda, Kalpatru; Singh, Prakash; et al. (ORYZA-An International Journal of Rice, 2022)
The facts pertaining to the inheritance of basic and value addition traits are prerequisite in designing much suited breeding strategies to harness substantial genetic gain in crop plants. The present study was aimed at comprehensive scrutiny of the quantitative traits, responding drought tolerance in rice through generation mean analysis (GMA). We have evaluated six generations ( P1, P2, F1, F2, B1 and B2) of cross, HUR-917 × DRR Dhan-42. The results revealed that all scales, A, B, C and D were significant for yield and attributing traits under irrigated and drought conditions, reflecting the presence of epistasis. Major yield contributing traits like days to 50% flowering (DFF), days to maturity (DM), plant height (PH), panicle length (PL), flag leaf length (FLL), number of grains per panicle (NGPP) and test weight (TW) showed the presence of duplicate epistasis under both conditions. Whereas, traits like the number of earbearing tillers (NEBT) and grain yield per plant (GYPP) shown duplicate epistasis under drought. The results suggest the prevalence of additive gene effect and non-allelic interactions/epistasis effect on the genetic control of majority of the yield traits. Additive (d) effect and dominant × dominant (l) gene interaction was the only significant portion of gene controlling grain yield per plant in the rice. The positive additive gene effect indicates that HUR-917 contributes more to the trait than DRR Dhan-42 and vice versa.